Systems analysis and design - Tilley, Scott R. (Scott Robert) 1964-; Rosenblatt, Harry J. (Cengage Learning, 2017)
This book covers traditional approaches to systems analysis and design and includes new emerging technologies, such as agile methods, cloud computing, and mobile applications.